Respuesta del pasto maralfalfa (pennisetum sp.) A dosis crecientes de n y s bajo condiciones del valle del río carrizal - Intriago Cobeña, Geovanni Fabricio (2018)
The present investigation was carried out in the conventional area of the experimental campus at "ESPAM MFL"; the objective of the investigation was to study the response of the maralfalfa grass (Pennisetum sp.) to the application of several levels of N and S in conditions of the Carrizal river valley. For this, Factor A (Nitrogen dose) and Factor B (Sulfur dose) were established. The study levels for factor A were: 0 kg of N ha-1; 250 kg of N ha-1; 500 kg of N ha-1 and 750 kg of N ha-1, while for factor B the following levels were established: 0 kg of S ha-1; 50 kg of S ha-1; 100 kg of S ha-1 and 150 kg of S ha-1. Urea (46% N) and Yesolina (18% S) were used for the application of the treatments. The trial was established under a randomized complete block design (DBCA) with factorial arrangement A (Nitrogen) x B (Sulfur) with three replicates per treatment, with a total of 48 experimental units. The variables were analyzed: plant height, fresh biomass yield and bromatological analysis. According to the results of the experiment, the effect of the nitrogen and sulfur levels had a significant effect on the yield variables in leaf biomass, stem biomass, leaves / stem ratio and fresh biomass, the values in these variables rise as increases the amount of nitrogen used, concluding that the best dose of nitrogen and sulfur for the fertilization of maralfalfa grass is 750 kg N ha-1 and 150 kg S ha-1.